Clodronate is not protective in lethal viral encephalitis despite substantially reducing inflammatory monocyte infiltration in the CNS - Spiteri, Alanna G.; van Vreden, Caryn; Ashhurst, Thomas M.; Niewold, Paula; King, Nicholas J. C. (Frontiers in Immunology, 2023)
Bone marrow (BM)-derived monocytes induce inflammation and tissue damage in a range of pathologies. In particular, in a mouse model of West Nile virus (WNV) encephalitis (WNE), nitric oxide-producing, Ly6Chi inflammatory monocytes from the BM are recruited to the central nervous system (CNS) and contribute to lethal immune pathology. Reducing the migration of these cells into the CNS using monoclonal antibody blockade, immune-modifying particles or CSF-1R inhibitors reduces neuroinflammation, improving survival and/or clinical outcomes. Macrophages can also be targeted more broadly by administration of clodronate-encapsulated liposomes, which induce apoptosis in phagocytes. In this study, clodronate reduced the inflammatory infiltrate by 70% in WNE, however, surprisingly, this had no effect on disease outcome. More detailed analysis demonstrated a compensatory increase in neutrophils and enhanced activation status of microglia in the brain. In addition, we observed increased numbers of Ly6Chi BM monocytes with an increased proliferative capacity and expression of SCA-1 and CD16/32, potentially indicating output of immature cells from the BM. Once in the brain, these cells were more phagocytic and had a reduced expression of antigenpresenting molecules. Lastly, we show that clodronate also reduces non-myeloid cells in the spleen and BM, as well as ablating red blood cells and their proliferation. These factors likely impeded the therapeutic potential of clodronate in WNE. Thus, while clodronate provides an excellent system to deplete macrophages in the body, it has larger and broader effects on the phagocytic and nonphagocytic system, which must be considered in the interpretation of data.